1997
DOI: 10.1097/00001756-199711100-00019
|View full text |Cite
|
Sign up to set email alerts
|

Optical imaging in vitro provides evidence for the minicolumnar nature of cortical response

Abstract: The response of rat neocortical slices to electrical stimulation at the layer VI/white matter border was recorded using intrinsic signal optical imaging. The optical response of the slice is column-shaped, extends from layer VI to the pial surface, and is strongly correlated with the amplitude of simultaneously recorded evoked potentials. Spectral analysis revealed radially oriented spatial variations in the intensity of the optical signal with a period of 30-60 microm/cycle. Nissl-stained sections of slices a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…We and others have previously shown that the IOS requires postsynaptic activation since the removal of Ca 2ϩ ions from the solution with which the slice is perfused leads to a total but reversible loss of the signal. 19,20 Similarly, the application of the glutamate receptor antagonists d-2-amino-phosphovaleric acid (D-APV, 100 mM) and 6-cyano-7-nitroquinoxaline-2,3-dione (CNQX, 10 mM) 11 or kynurenic acid (1.5 mM) 20 leads to an almost complete block of the IOS. Thus, the IOS does not appear to reflect antidromic activity directly.…”
Section: Functional Imaging Of Cortical Connectivitymentioning
confidence: 99%
See 4 more Smart Citations
“…We and others have previously shown that the IOS requires postsynaptic activation since the removal of Ca 2ϩ ions from the solution with which the slice is perfused leads to a total but reversible loss of the signal. 19,20 Similarly, the application of the glutamate receptor antagonists d-2-amino-phosphovaleric acid (D-APV, 100 mM) and 6-cyano-7-nitroquinoxaline-2,3-dione (CNQX, 10 mM) 11 or kynurenic acid (1.5 mM) 20 leads to an almost complete block of the IOS. Thus, the IOS does not appear to reflect antidromic activity directly.…”
Section: Functional Imaging Of Cortical Connectivitymentioning
confidence: 99%
“…Other studies using IOS imaging in vitro have reported only on the properties of neocortical response to repetitive afferent drive delivered at the layer VI/WM border. 11,15,16,19 As a result, some confusion has arisen as to the spatial specificity of the intrinsic optical signal. However, the similarity of our images of functional cortical connectivity with those obtained using voltage-sensitive dye imaging, as well as our observation that the IOS elicited by layer VI/WM stimulation contains minicolumn-scale periodicities, 19 suggests that the IOS has substantial spatial resolution.…”
Section: Comparison With Other Anatomical Neurophysiological and Opmentioning
confidence: 99%
See 3 more Smart Citations